Production cross-sections of Re-186 radionuclide from the proton bombardment on natural tungsten - Khandaker, Mayeen Uddin; Kim, G.; Uddin, M.S.; Kim, K.; Lee, M.; Kim, K.S.; Lee, Y.Y.; Cho, Y.S.; Lee, Y.O. (2008)
The excitation function of the W-nat(p,xn)Re-186 nuclear reaction was measured as a function of the proton energy in the range of 6-40 MeV by using a stacked-foil activation technique combined with high-purity germanium gamma-ray spectroscopy at the MC50 cyclotron of the Korea Institute of Radiological and Medical Sciences. The present results are in good agreement with the earlier reported experimental data and the theoretical calculation based on the TALYS code. The thick target integral yield was also deduced from the measured excitation function and stopping power of W-nat over the energy range from threshold up to 40 MeV.